Building Information Modeling—Enabled Construction Safety Culture and Maturity Model: A Grounded Theory Approach - Olugboyega, Oluseye; Windapo, Abimbola (Frontiers in Built Environment, 2019)
The study examines the dimensions and components of construction safety culture and whether the application of BIM technologies to the dimensions of construction safety culture improves the safety maturity levels among construction workers. The study employed a systematic literature review and grounded theory in achieving the research objectives. The dimensions and components of construction safety culture were found to comprise of a safety management system, safety behaviour, and safety climate. A bim-enabled conceptual model of construction safety culture was developed as an output of the study. The model demonstrates how the dimensions of construction safety culture change the maturity levels of safety among construction workers as enabled by BIM technologies. The model has implications for improved construction safety management practices through the use of BIM on construction projects. The study concludes with implications for practice and future research.